2020
DOI: 10.3389/fphar.2020.00648
|View full text |Cite
|
Sign up to set email alerts
|

Use of Opioids Increases With Age in Older Adults: An Observational Study (2005–2017)

Abstract: Aim: Pain is increasingly treated with opioids. Potential harms of opioid therapy disproportionally affect older patients. This study aims to provide information on trends, nature and duration of opioid prescribing to older adults, in primary care and to explore differences between older patients from different ages. Methods: Primary care data (2005-2017) were derived from routine electronic medical records of patients in Nivel Primary Care Database. All opioid prescriptions with Anatomical Therapeutic Chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Clinical decision tools can support prescribers in rational (de-) prescribing decision making. from 1.3 to 7.0% [19]. The increase was highest among persons aged 85 years and over.…”
Section: Key Pointsmentioning
confidence: 86%
“…Clinical decision tools can support prescribers in rational (de-) prescribing decision making. from 1.3 to 7.0% [19]. The increase was highest among persons aged 85 years and over.…”
Section: Key Pointsmentioning
confidence: 86%
“…First, the number of patients in the elderly population increased. Age is closely associated with increasing opioid consumption [24]. Studies from European countries between 2000 and 2010 reported that consumption of strong opioids was highest among patients aged 66-80 years [21,25].…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy, androgen receptor-targeted drugs, and radionuclides were used to indicate CRPC because it was the only indication for these treatments during the study period. Initially, we included bone pain and opioid use in our assessment because bone pain is often present in men with metastatic PCa, but we subsequently excluded these factors as they are not specific for PCa progression, especially in older men with multiple comorbidities [26,27].…”
Section: Discussionmentioning
confidence: 99%